Comparison of sintering condition and radio frequency plasma discharge on the conversion of coal/biomass fly ash into high-temperature thermal energy storage material. (15th July 2019) - Lin, Wenlin Yvonne; Li, Tao; Akasyah, Luqman; Lim, Jian Wei Mark; Xu, Haoxin; Py, Xavier; Rawat, Rajdeep Singh; Romagnoli, Alessandro
Highlights: Radio Frequency plasma improved the thermal properties of Coal Biomass Fly Ash. Compared to vitrification method, Radio Frequency plasma is less energy intensive. Conventional sintering is not sufficient to improve the thermal properties. As a waste, processed Coal Biomass Fly Ash offers quite high energy density. The processes studied shows Coal Biomass Fly Ash is comparable to natural resource. Abstract: The management of solid waste has become increasingly challenging with the accelerated growth in residency in Singapore. Alternative utilization, such as high temperature thermal energy storage material, valorizes the waste to the status of a new resource, thereby reducing the need of virgin material and ensuring sustainability. In Singapore, coal is co-fired with biomass and the coal/biomass fly ash is partially reused and the rest is landfilled. This research evaluated two different fabrication routes: conventional sintering and plasma processing. The novelty of this study is that unlike most studies whereby plasma arc is used to melt the ash at high temperature, in this study, a 13.56 MHz radio frequency plasma is used to control discharge parameters through in-situ diagnostics of active species density and temperatures. This allows for high throughput and uniform processing. An optimized plasma process could potentially reduce the total number of processing phases, with a lower energy budget for processing, while increasing the controllability of the processes to achieve the desired material properties. The chemical composition, and the thermal properties such as specific heat capacity, energy density and thermal conductivity of the ceramics made from coal/biomass fly ash were evaluated. Experimental evaluation shows that the radio frequency plasma processed coal/biomass fly ash samples were found to improve the thermal properties of coal/biomass fly ash in general. It is hypothesized that the mechanism of improvement from radio frequency plasma was due to the incorporation of hydrogen into the material and the conversion of mineralogical composition (i.e. quartz) which gave rise to the better performance. In conclusion, this study has shown the potential of using coal/biomass fly ash as thermal energy storage material through innovative process such as radio frequency plasma discharge.